Magnetoelectric effects in magnetic films with alternating magnetic anisotropy: the emergence and stability of Bloch points - Gareeva, Zukhra; Filippova, Viktoria; Shulga, Nikolai; Doroshenko, Rurik (Physical chemistry chemical physics : PCCP, 2024)
Magnetic topological states are a subject of intense investigation due to their potential for advancing scalable logic and information storage technologies. In this article, we investigate topological defects in magnetic films, focusing on Bloch point-like singularities in magnetization distribution with significant implications for magnetoelectric and ferroelectric properties. We explore exchange-coupled ferromagnetic films composed of alternating magnetic layers with distinct in-plane and out-of-plane magnetic anisotropy. Through micromagnetic simulations, we analyze the magnetization reversal processes and the emergence of Bloch point-like configurations induced by external magnetic fields. We identify the conditions necessary for stabilizing these states and elucidate their ferroelectric properties. Our study reveals that Bloch points act as sources of electrical charge due to the inhomogeneous distribution of magnetization, offering opportunities for implementing their electric properties in future devices. Magnetic topological states in exchange-coupled ferromagnetic film in the absence of the Dzyaloshinsky-Moriya interaction are investigated and the conditions required for the existence of Bloch point states are determined.